2020
DOI: 10.1177/1469540520902508
|View full text |Cite
|
Sign up to set email alerts
|

The changing meaning of millets: Organic shops and distinctive consumption practices in Bengaluru, India

Abstract: The number of organic shops in Bengaluru has increased remarkably in the last few years, with millets being the main products drawing consumers. Yet, organic shops are only attracting middle-class consumers. We observed and interviewed 104 customers in five organic shops in Bengaluru to find out why this is the case. In this article, we follow practice theory to discuss the reported consumption patterns. We show that consumers, influenced by commercials and the advice of medical and nutritional professionals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
0
25
0
4
Order By: Relevance
“…Sz} ucs et al (2016) found that Hungarian consumers acquired health information from the Internet, such as that foods containing a high fibre content are good for the body; in contrast, Romanian consumers stated that television was their primary source for information on what constitutes healthy food. Consumers chose to include millets in their everyday diet when recommended to do so by doctors and nutritional professionals (Erler et al, 2020).…”
Section: Consumption Of Alternative Staplesmentioning
confidence: 99%
“…Sz} ucs et al (2016) found that Hungarian consumers acquired health information from the Internet, such as that foods containing a high fibre content are good for the body; in contrast, Romanian consumers stated that television was their primary source for information on what constitutes healthy food. Consumers chose to include millets in their everyday diet when recommended to do so by doctors and nutritional professionals (Erler et al, 2020).…”
Section: Consumption Of Alternative Staplesmentioning
confidence: 99%
“…Regarding the consumption side in Southern AFNs, two aspects have been discussed in the literature so far: (1) The role of AFNs' consumers and (2) their relationship to the AFNs' producers. Newly developed Southern AFNs in particular are at risk of remaining a niche development as their consumers are often part of very specific middle-to upper-class groups [2,14]. Furthermore, in much of the Global South, farmers' livelihoods are uncertain, so improvement of livelihoods should probably take priority over producer-consumer relationships [15].…”
Section: Southern Afn In Researchmentioning
confidence: 99%
“…For example, is it sufficient for consumers to simply meet the farmer in order to establish trust, or do they also have to visit the farm? For Bengaluru, we have discussed this elsewhere in more detail [14].…”
Section: Southern Afn In Researchmentioning
confidence: 99%
See 2 more Smart Citations